Determinación de compuestos benzodiacepínicos en muestras de aspirado gástrico por el método de cromatografía en capa fina, que ingresan al laboratorio de química forense del departamento de criminalística de la policía judicial de chimborazo durante el periodo comprendido de enero a junio 2013. - Macas Anguieta, Víctor Hugo (2013)
The increased number of factors have led currently in people increased stress level anxiety, insomnia, and nervousness developing diseases, etc.In which there foster increased consumption of benzodiazepine compounds, creating dependency in the same short time, therefore an increase in poisoning by improper use without medical supervision in order to create a state of calm and relaxation.